Pengaruh Senam Otak (Brain Gym) Terhadap Tingkat Demensia Pada Lansia - Sarifah Dwi Wulan Septianti; Suyamto; Teguh Santoso (Jurnal Keperawatan Notokusumo, 2016)
Background: Dementia can affect daily activity ability because it consists of an array of symptoms such as decrease in cognitive function, mood swings, and in behaviors. One of the changes in cognitive function that happens among senior citizens is declining memory, therefore, a brain gym needs to be introduced to senior citizens to reduce the level of dementia. Method: This was a quasi-experimental research which used non randomized control group pretest-posttest design. The number of respondents in the experiment group was 19 and the number of respondents in the control group was 19. This research was carried out in the work area of Ngaglik I Integrated Health Post, especially in Mrisen Senior Citizen Integrated Health Post, Sardonoharjo and Lele Senior Citizen Integrated Health Post, Minomartani, Ngaglik, Sleman, from April to June 2015. Result: The results of statistics test on the average score of dementia level from the experiment group was higher as compared with the score from the control group, the average score from the experiment group was 3.7895, whereas the average score from the control group was 2.6316. Therefore, the difference between the average scores from the experiment group and the control group was 1.1579. The result of Independent Samples T-Test correlation on the experiment group showed that the value of t = 4.610 and the p-value = 0.000, which means that there was a significant influence from brain gym on the dementia level, because the p-value was smaller than alpha, the p-value was 0.000 <0.05 (?), therefore Ha was accepted and Ho was rejected. Conclusion: There was a significant influence from brain gym on the level of dementia among senior citizens.